Simulation of seawater intrusion in Jifara Plain, Libya - Elaswed, Nadia Ahmed (2018)
In Libya, the limited recharge and increasing water demand have resulted in overexploitation of groundwater storage in the Tripoli aquifer, Jifara plain. The consequences of the aquifer’s over-exploitation are serious declines in groundwater levels and deterioration in groundwater quality. The Tripoli aquifer, Jifara plain, is an unconfined aquifer located Northwest of Libya with a total area of 763 km2. The Tripoli aquifer includes five well profiles, which are: Al Mayah profile (7 wells), Janzur profile (9 wells), Gergaresh profile (10 wells), Eyn Zarah profile (8 wells), and Tajura profile (10 wells) besides 21 wells distributed between them. In total, there are 65 pumping wells in the Tripoli aquifer. The ModelMuse model was calibrated, validated, and applied to predict groundwater levels and TDS concentrations in the Tripoli aquifer, Jifara plain. The simulation results are used to assess the current and future conditions of the aquifer. The geological, hydrogeological, and hydrological data used in the simulation processes were acquired from the Libyan General Water Authority. For the Tripoli aquifer, simulation of future management scenarios under transient state were carried out to study the impact of pumping on groundwater levels and TDS concentrations for a period of 90 years (2010-2100). In this study, three possible pumping scenarios from the Tripoli aquifer were simulated using ModelMuse model. The first scenario was based on using the current pumping rate from the wells of the Tripoli aquifer, which was estimated to be 74.35×106 m3/yr as a fixed pumping rate up to 2100. The second scenario was based on using varying pumping rates (74.35×106 m3/yr in 2010 and 152.65×106 m3/yr in 2100), which took into account the population growth for 90 years (2010-2100). The third scenario was based on using a fixed pumping rate of 19×106 m3/yr, which is equivalent to the annual recharging rate in the Tripoli aquifer. The annual recharging in the Tripoli aquifer was recommended to be taken as 10% from the annual rainfall. Simulation results showed that for fixed pumping rare (first scenario), the maximum drop in groundwater level, TDS concentration and the aquifer affected area by seawater intrusion were 13.2 m (found in Al Mayah profile, well number T106), 25817 mg/l (found at the wells located in Al Mayah profile), 694 km2 respectively. For future increased pumping rate (second scenario). The simulation results showed that the maximum drop in groundwater level, TDS concentration and the aquifer areas affected by seawater intrusion were 15.4 m (found in Al Mayah profile, well number T106), 37783 mg/l (found at the wells located in Al Mayah profile) and 727 km2 respectively. When the pumping rate was equivalent to the recharging rate at the Tripoli aquifer (third scenario), simulation results indicated a considerable increase in groundwater level, which was found to be 3.5 m while the decrease in TDS concentration in the areas affected by seawater intrusion were 13928.8 mg/l and 172 km2. Among the simulated pumping scenarios, sustainable pumping rate of 19×106 m3/year was recommended since it would result in a considerable rise in groundwater level and a noticeable decrease in TDS concentration. Besides, following this scenario, augmentation of water from other sustainable management practices such as rainwater harvesting should be followed in order to control the problem of seawater intrusion in the Tripoli aquifer.